Partial purification of cyclodextrin glucanotransferase from alkalophilic Bacillus sp. TS1-1 - Mohd Azim, Abdul Rahman (2008)
The cyclodextrin glucanotransferase (CGTase; EC 2.4.1.19) from Bacillus sp. TS1-1 has been partially purified from crude culture by centrifugation and cross-flow filtration. Initial 72.96 U/ml of CGTase was detected in the culture after 24 hours of incubation. The crude supernatant obtained after centrifugation for 5000 rpm, 5 minutes and 4°C was subsequently filtered at 15°C through cross-flow filtration using Kvick Lab cross-flow system. Two cassettes were used with molecular weight cut off of 50K and 10K. The retentate from 50K cassette was further filtered through 10K cassette. Each permeate and retentate from each cassette were tested for CGTase activity. The highest CGTase activity was detected at retentate of 10K cassette which suggested an initial size of CGTase between 10 kDa and 50 kDa. The crude and partially purified enzyme was then subjected to electrophoresis (SDS-PAGE). It was clear that a large amount of proteins had been removed by cross-flow filtration. Based on this work, the crude enzyme was purified 5.57 fold using cross-flow filtration.